PERANCANGAN SISTEM INFORMASI PEMBAYARAN ANGSURAN KREDIT SEPEDA MOTOR BERBASIS LAN PADA CV. SUMBER JAYA KENCANA MOTOR BINJAI - Abdur Rahman (STMIK KAPUTAMA, 2023)
With the development of economic activity lately, it is increasingly triggering economic activity in all fields. Among these economic activities are business activities in the field of selling automotive products. So that at this time many emerging companies engaged in the field of automotive loan financing. And one such company is CV. Sumber Jaya Kencana Motor Binjai which is also the official distributor for sales of Yamaha motorcycles. Purchasing motorcycles on credit is more likely to bring greater results than purchasing in cash. In installment payments, there is an agreement to protect the seller from the possibility of uncollectible receivables. To protect the interests of the seller from the possibility of non-fulfillment of the obligations that must be fulfilled by the buyer, an agreement or installment sales contract is made after the transaction is carried out, then a penalty calculation is made where the fine is calculated from the number of installments paid per month multiplied by 0.5% and the result is the number per day late payment of consumer installments. The most important factor in the data processing process is in terms of motorcycle installment payments where in this case the company still uses 2 payment methods, namely direct payments to CV dealers. Sumber Jaya Kencana Motor Binjai, namely through cashiers and payments through collectors. In this process the input is still inaccurate and data errors often occur, because there is no program that can assist cashiers in inputting motorcycle installment payments and the system used is not efficient. Another problem is that fraud is still very prone to occur in terms of installment payments, where the cashier as someone who is very responsible for this payment also has the opportunity to cheat because there is no accurate system in terms of inputting data. Seeing this, the authors are very interested in designing a motorcycle payment information system with the title